Facilitating the reuse process in an object oriented environment by learning from observation. - Rovel, Thierry. (University of Ottawa (Canada), 1993)
The aim of this research is to ease the reuse of components in an Object-Oriented library. We ease the three main processes included in reuse: searching for, understanding and adapting components. The novelty of this approach is that all the information needed to achieve these improvements is learned automatically by spying on the programmer's actions. This thesis describes a model for a learner in an Object-Oriented environment. A specific implementation for the Smalltalk language, called LEARNIST (Learning to EAse Reuse IN SmallTalk), is described and illustrated with examples.
Keywords: Computer Science.